Development and validation of a Social Images Evaluation Questionnaire for youth in residential care - Lopes, D.; Calheiros, M. M.; Patrício, J.; Garrido, M. V. (PLoS One, 2017)
Social images are defined as prevailing shared ideas about specific groups or societies without concrete or objective evidence of their accuracy or truthfulness. These images frequently have a negative impact on individuals and groups. Although of outmost importance, the study of the social images of youth in residential care is still scarce. In this article we present two studies for the development and validation of the Social Images Evaluation Questionnaire (SIEQ). In study 1, participants were asked to freely generate words that could be associated to youth in residential care in order to obtain a list of attributes to be used in the SIEQ. In study 2, the main psychometric characteristics of the SIEQ were tested with samples of laypeople and professionals. The main results support the proposal of a new and psychometrically sound measurement -the SIEQ-to analyze the social images of youth in residential care.